2001
DOI: 10.1161/hh1901.097084
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Suppresses Endothelial Nitric Oxide Synthase and Upregulates Endothelin-Converting Enzyme-1 Expression by Distinct Pathways

Abstract: Abstract-An imbalance of nitric oxide and endothelin plays an important role in cardiovascular disease. Thrombin exerts profound effects on endothelial function. The present study investigated the molecular mechanisms by which thrombin regulates endothelial nitric oxide synthase (eNOS) and endothelin-converting enzyme (ECE)-1 expression in human endothelial cells. Incubation of human umbilical vein endothelial cells with thrombin (0.01 to 4 U/mL) for 15 to 24 hours markedly downregulated eNOS and increased ECE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
3
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 44 publications
8
127
3
3
Order By: Relevance
“…This was inhibited by a statin, and GGPP reversed the suppressive effect of a statin on RhoA activation induced by lysophosphatidylcholine (11). Taken together with previous reports (4,7,17,20), our results suggest that, in ECs, receptor agonist-induced rapid activation of unprocessed GDP-RhoA occurs through stimulation of two sequential steps, geranylgeranylation of RhoA and GDP/GTP exchange in RhoA.…”
Section: Fig 6 Cytoskeleton Analyses By Tritc-phalloidin Stainingsupporting
confidence: 88%
See 1 more Smart Citation
“…This was inhibited by a statin, and GGPP reversed the suppressive effect of a statin on RhoA activation induced by lysophosphatidylcholine (11). Taken together with previous reports (4,7,17,20), our results suggest that, in ECs, receptor agonist-induced rapid activation of unprocessed GDP-RhoA occurs through stimulation of two sequential steps, geranylgeranylation of RhoA and GDP/GTP exchange in RhoA.…”
Section: Fig 6 Cytoskeleton Analyses By Tritc-phalloidin Stainingsupporting
confidence: 88%
“…We and others (4,7,20) demonstrated that thrombin activated RhoA in ECs within 0.5-5 min and increased GEF activity within 1 min in HEK-293T cells (20,35). Holinstat et al (20) showed that thrombin phosphorylated p115RhoGEF in human umbilical vein ECs within 1 min.…”
Section: Discussionmentioning
confidence: 80%
“…20 However, in contrast to Y27632, which did not affect basal eNOS expression, 20 we found that treatment with hydroxyfasudil alone increased basal eNOS expression without apparently affecting basal Rho-kinase activity. These findings suggest that hydroxyfasudil may have additional Rho-kinase-independent effects on eNOS expression.…”
Section: Discussioncontrasting
confidence: 55%
“…72 Furthermore, long-term treatment with thrombin was shown to downregulate the expression of eNOS in endothelial cells. 72,73 Alternatively, a dual receptor system for thrombin in the endothelial cells (PAR1 and PAR4) 18 may explain the thrombin-induced Ca 2ϩ -independent and dependent production of NO. The stimulation of PAR4 has been reported to induce NO production without a concomitant elevation of [Ca 2ϩ ] i in endothelial cells.…”
Section: Pars-mediated Production Of Nitric Oxide In Endothelial Cellsmentioning
confidence: 99%